2020
DOI: 10.3390/fib8060041
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Strengthening of RC Continuous T-Beams Using CFRP

Abstract: In this paper, experimental investigations for strengthening reinforced concrete (RC) continuous beams were performed. Eighteen T-beams were cast, twelve of which were inverted T-beams where the flange portion of the T-beam was subjected to positive flexure to represent the support region of a continuous beam. Six of the T-beams were non-inverted where the web is subjected to positive flexure. Carbon fiber reinforced polymer (CFRP) sheets with different widths were considered, and different strengthening confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…The strengthening of structural members to enhance their capacity and service life using FRP has been proven to be an effective technique. There are many different types of FRP and strengthening methods available, but strengthening structures via the use of externally bonded FRP has become very popular worldwide [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The strengthening of structural members to enhance their capacity and service life using FRP has been proven to be an effective technique. There are many different types of FRP and strengthening methods available, but strengthening structures via the use of externally bonded FRP has become very popular worldwide [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As well as, the dominant failure mode in the strengthened beam with nonprestressed FRP materials was debonding interfacial, but in the beam that was strengthened by prestressed FRP materials was tensile rupture of the CFRP sheet. Al-Khafaji and Salim [11] proved that as the ratio of the width of CFRP to the width of concrete increased, the ultimate load and stiffness for continuous Tbeams strengthened with CFRP enhanced. Strengthening by CFRP for preloading 100% and 90% beams can be enhanced the load capacity by 51.5% and 68.5% respectively [12].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] A typical FRP material used for retrofitting is carbon fiber-reinforced polymer (CFRP). Some existing experimental studies [9][10][11][12][13] have indicated that CFRP offered great performance in the improvement of the mechanical behavior of RC structures.…”
Section: Introductionmentioning
confidence: 99%